2018
DOI: 10.1016/j.celrep.2018.04.045
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β Regulates Brain Energy Metabolism

Abstract: SUMMARY GSK3β is a serine threonine kinase implicated in the progression of Alzheimer’s disease. Although the role of GSK3β in growth and pathology has been extensively studied, little is known about the metabolic consequences of GSK3β manipulation, particularly in the brain. Here, we show that GSK3β regulates mitochondrial energy metabolism in human H4 neuroglioma cells and rat PC12-derived neuronal cells and that inhibition of GSK3β in mice in vivo alters metabolism in the hippocampus in a region-specific ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…Moreover, GSK3β inhibition alters PGC-1α protein stability, localization, and activity. These studies support the idea that GSK3β may be important in neuronal metabolic integrity [ 55 ].…”
Section: Role Of Gsk3β Signaling In Neuronssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, GSK3β inhibition alters PGC-1α protein stability, localization, and activity. These studies support the idea that GSK3β may be important in neuronal metabolic integrity [ 55 ].…”
Section: Role Of Gsk3β Signaling In Neuronssupporting
confidence: 85%
“…GSK3β regulates PGC-1α stability through phosphorylation, which can be recognized by the E3 ubiquitin ligase [ 54 ]. Several studies have shown that GSK3β regulates mitochondrial energy metabolism in the neurons and glia [ 55 ]. Moreover, GSK3β inhibition increases mitochondrial respiration and membrane potential, and alters NAD(P)H metabolism in the neurons.…”
Section: Role Of Gsk3β Signaling In Neuronsmentioning
confidence: 99%
“…GSK3β is a serine/threonine protein kinase with broad expression and one of the downstream targets of Akt. It is essential in energy metabolism (Martin et al, 2018) and nerve cell development (Chen et al, 2019a). The levels of GSK3β can be decreased by phosphorylation at the ser9 site (Xu et al, 2017;Chen et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Since p-tau S396 did not significantly change with 12 weeks of aerobic training, other pathologic phosphoepitopes induced by GSK3β Y216 could be evaluated with further study. Another possibility of the mismatch between the levels of phosphorylated tau and p-GSK3βY216 could be the long-term effects of aerobic training on brain metabolism, since GSK3β plays a crucial role in metabolism [26]. In fact, the level of IRS-1 in the IC of RG was significantly higher than that of SG, indicating that a 12-week aerobic training may regulate brain metabolism as well as tau protein modification.…”
Section: Discussionmentioning
confidence: 99%